An integrated approach toward testing sports equipment - Sevrez, V.; Rao, G.; Vigouroux, L.; Reinoud; Bootsma, J.; Berton, E. (The Engineering of sport 7, Volume 2, 2008)
Recent improvements in material technology, together with generalization of testing, prototyping, and benchmarking, have impacted on performance in many Sports. However, sports equipment properties are often tested through mechanically based standardized protocols. Such protocols would ignore the effects on equipment resulting from mechanically unpredicted manoeuvres performed by athletes aiming for performance, injury protection or comfort. Their use may thus turn out to be of limited use in the evolution of sports equipments towards perfection, as a first-rate equipment is not only the one including high-tech materials but also the one interacting in the best way with the athlete using it. This study aimed at determining, through the example of the backward giant circle on the high bar, whether or not the effects of standardized tests on sports equipment are comparable with the effects caused by real athletic practice. A comparison between the characteristics of the kinematics predicted from a pure mechanical analysis of the giant circle and those observed in real situations during performance of giant circles by seven elite gymnasts' pointed out differences. According to the mechanical analysis, the gymnasts should be maximally extended at vertical handstand and maximally flexed at the moment of passing through the lower point upwards. Maximal extension in fact occurred when their body center of mass had rotated approximately 120° from the handstand and maximal flexion occurred approximately 100° after having passed through the lower point. This result suggests that manufacturers should realize that standardized test only provide limited Information, as differences in kinematics between the predicted and observed solution are associated with differences in the force exerted. Integration of the effect of intentional actions of the athlete using the equipment as a constraint in test procedures would render these more comprehensive thus allowing development of more efficient equipment.